The Enigma of Crohn’s Disease: a case report - Azmi, Nabil; Tiew Toot Chaw, Warren; Abdul Rahman, Nurafdzillah; Zaihan, Sumayyah; Ahmad Kammal, Wan Syahira Ellani (Springer, 2024)
Crohn's disease (CD) is an inflammatory condition affecting the gastrointestinal tract, often leading to persistent inflammation in various parts, notably the terminal ileum and colon. Clinical manifestations of CD can become complex due to complications like strictures, fistulas, and perianal abscesses. The disease typically exhibits transmural inflammation and skip lesions, where unaffected areas alternate with affected ones. Treatment goals focus on achieving disease remission and preventing complications that may require surgical intervention. Surgery becomes crucial in managing complications such as Crohn's strictures and perforations. Here, we describe a challenging case involving a young woman who underwent surgery for abdominal abscess and with Crohn’s stricture and fistula.